2017
DOI: 10.1186/s13023-016-0558-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, biochemical and molecular characteristics of Filipino patients with mucopolysaccharidosis type II - Hunter syndrome

Abstract: BackgroundMucopolysaccharidosis type II, an X-linked recessive disorder is the most common lysosomal storage disease detected among Filipinos. This is a case series involving 23 male Filipino patients confirmed to have Hunter syndrome. The clinical and biochemical characteristics were obtained and mutation testing of the IDS gene was done on the probands and their female relatives.ResultsThe mean age of the patients was 11.28 (SD 4.10) years with an average symptom onset at 1.2 (SD 1.4) years. The mean age at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
13
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
9
13
2
1
Order By: Relevance
“…However, the clinical profiles of the MPS II patients (P1-P7) were in agreement with several studies described in the literature, and the clinical manifestations of the phenotype of Hunter syndrome ranged from moderate to severe Hunter syndrome phenotypes [13].…”
Section: Clinical Biochemical and Molecular Correlations In Mps II Psupporting
confidence: 88%
“…However, the clinical profiles of the MPS II patients (P1-P7) were in agreement with several studies described in the literature, and the clinical manifestations of the phenotype of Hunter syndrome ranged from moderate to severe Hunter syndrome phenotypes [13].…”
Section: Clinical Biochemical and Molecular Correlations In Mps II Psupporting
confidence: 88%
“…Neurological degeneration was found in 23.3% of 77 South American MPS II patients, while Chiong et al. found that 91.3% of Filipino MPS II patients revealed development delay/mental disorders.…”
Section: Discussionsupporting
confidence: 78%
“…In the literature, behavior disorders such anxiety, hyperactivity, aggression, and sleep upset have been reported. 1,3 Neurological degeneration was found in 23.3% of 77 South American MPS II patients, 14 while Chiong et al 15 found that 91.3% of Filipino MPS II patients revealed development delay/mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing different geographic regions showed us that MPS III and MPS I were detected frequently in Tunisia (14) while MPS VI was relatively more common in Egypt, different from the other countries (15). Australian studies revealed MPS III and MPS I (16) as the most common types; and MPS II was the most common type in the Philippines (17). As for the studies in our country, the most common types of MPS detected by several authors (18) (18,20).…”
Section: Discussionmentioning
confidence: 99%
“…Physical examination findings showed that the most commonly detected clinical findings were coarse facial appearance, skeletal findings, and hepatosplenomegaly. In the literature, published demographic studies involving different types of MPS reveal the most common clinical findings as follows: coarse face, corneal opacity, macroglossia in MPS I (21); short stature, joint stiffness, and coarse facial appearance in MPS II (17); growth retardation, coarse face, hepatosplenomegaly in MPS III (22); short stature, limited joint movement, pectus carinatum in MPS IV (23); coarse face, joint and skeletal abnormalities in MPS VI (24). In our study, since the number of patients with subtypes of MPS was limited, no differentiation based on subtype could be made.…”
Section: Discussionmentioning
confidence: 99%